Abraham as spiritual ancestor : a postcolonial Zimbabwean reading of Romans 4 - Kamudzandu, Israel. (Biblical Interpretation Series, 2010)
New Testament commentaries and exegetes have not paid sufficient attention to the context in which Paul's Epistel to the Romans was crafted. This book written from an African perspective offers a fresh interpretation on a contextualizing reading of Romans and its theology. The argument of the book is that Paul's construcntion of Abraham as a Spiritual ancestor of \'all\' faith people was based on his encounter with the Roman Ideology based on Aeneas as the founder of Rome. A juxtaposition of these two canonical ancestors needs to be considered in our 21st multi - ethnic Christian world. Paul's epitsle is not about how God saves the individual human being; rather the debate between Paul and the Jewish - Christian interlocutor is about how families of people and nations establish a kinship with God and one another. The concern with ancestors is apaque to Western Biblical readers and Christians. This is book helps both Westerners and Africans to value ethnic diversity.